2006
DOI: 10.1063/1.2181633
|View full text |Cite
|
Sign up to set email alerts
|

Quality factor control of Si-based two-dimensional photonic crystals with a Bragg mirror

Abstract: We have investigated the coupling between two-dimensional photonic crystals and a distributed Bragg reflector by fabricating silicon-based photonic crystals on top of a one-dimensional Bragg mirror. The two-dimensional photonic crystals contain Ge/ Si self-assembled islands as an internal source covering the 1.1-1.6 m spectral range. We show that we can control the quality factor of Bloch modes by varying the thickness of the silicon layer on top of the Bragg mirror. Quality factors up to 2200 are obtained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…An example of such characterization in original 2,5 D photonic crystals is given in Ref. [13]. As compared to studies undertaken with III-V materials, the GeSi self-assembled islands are an indirect band gap material with an intrinsically reduced radiative efficiency.…”
Section: Interest Of the Internal Source Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…An example of such characterization in original 2,5 D photonic crystals is given in Ref. [13]. As compared to studies undertaken with III-V materials, the GeSi self-assembled islands are an indirect band gap material with an intrinsically reduced radiative efficiency.…”
Section: Interest Of the Internal Source Techniquementioning
confidence: 99%
“…Despite this drawback, it has been shown that the photoluminescence of Ge/Si self-assembled islands embedded in nanocavities can be used to characterize the photonic crystals over a broad spectral range, from 1.2 to 1.6 μm, and this even at room temperature. Different type of defect-cavities or two-dimensional photonic crystals without defects have been investigated by this method [11,12,13]. The method requires to epitaxially grow a layer of Ge/Si self-assembled islands before processing of the photonic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The 225 nm thickness corresponds for the vertical one-dimensional stacking to a maximum amplitude of the electric field in the silicon layer for a wavelength of 1150 nm. Whereas only broad resonances are observed for the 170 nm sample, optical modes with a narrow linewidth corresponding to a quality factor value of 2200 is observed for the 225 nm sample [7]. This quality factor depends on the air filling factor of the photonic crystal and is experimentally maximum for a r/a ratio (hole radius divided by lattice parameter) of 0.28.…”
Section: Methodsmentioning
confidence: 81%
“…However, most of the researches are being conducted on the compound semiconductors. Only a few works [15][16][17][18] are reported for silicon-based materials.…”
Section: Introductionmentioning
confidence: 98%
“…Photonic crystal (PhC) microcavity can solve these problems in principle. In recent years, various optical microcavities, such as micro-disk [9,10], micro-sphere [11], and photonic crystal (PhC) microcavities [12][13][14][15][16][17][18] have been used to enhance the spontaneous emission. Inside optical microcavities, particular discrete resonant wavelengths are selected and enhanced, while the other wavelengths are suppressed due to the Purcell effect [19].…”
Section: Introductionmentioning
confidence: 99%